Penguatan Manajemen Pendidikan melalui Pendampingan Kegiatan Seni Al-Banjari untuk Meningkatkan Ketermapilan pada Kelompok Ibu-ibu di Desa Sladi Kecamatan Kejayan - Muhammad Bustomy; Nelud Darajatul Aliyah (ARDHI : Jurnal Pengabdian Dalam Negri, 2024)
This community service activity aims to improve the skills and quality of education management in groups of mothers through Al-Banjari arts assistance. Al-Banjari art, as a form of Islamic art, is not only a means of cultural expression, but also a medium for strengthening character education and social skills. The methods used in this program include needs identification, arts management training, direct practice, and evaluation. The results of the activity showed an increase in the mothers' skills in playing Al-Banjari art as well as their ability to manage art groups independently. Apart from that, this activity also has a positive impact on strengthening solidarity and self-confidence of participants. Thus, this program makes a real contribution to strengthening non-formal education based on local arts and culture.